Pengaruh Capital Expenditure, Special Allocation Fund, General Allocation Fund dan Level of Regional Financial Independence - Rianto -; Heryanto - (AKRUAL : Jurnal Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of Capital Expenditures, Special Allocation Funds, General Allocation Funds on the Level of Regional Financial Independence in D.I Yogyakarta Province in 2014-2021. The samples used in this study were all regencies/cities in the Province of D.I Yogyakarta using the census sampling technique. The independent variables of this study are Capital Expenditures, Special Allocation Funds and General Allocation Funds. The dependent variable of this study is the Level of Regional Financial Independence. The results show that capital expenditure has no effect on the level of regional financial independence, while the Special Allocation Fund has a significant negative effect on the level of regional financial independence, and the general allocation fund has a significant negative effect on the level of regional financial independence